Recreational activities to strengthen the workplace climate in the school context. (RIAF. International Journal of Physical Activity, 2025)
This study evaluated the impact of recreational activities on the work environment of teachers at the "Replica Aguirre Abad" Fiscal Educational Unit in Ecuador, with the aim of analyzing how a positive environment influences the cohesion and satisfaction of the teaching team. Using a quantitative approach and a descriptive-correlational design, a 30-item questionnaire was applied to 45 teachers. The data, processed with SPSS, revealed high reliability (α = 0.9035) and a significant relationship between a positive work environment and teacher well-being.The results highlighted that a favorable work environment increases satisfaction, cohesion, and interpersonal relationships among teachers. In addition, recreational activities proved essential to reduce stress and foster collaboration in the educational environment. This study supports the implementation of school policies that integrate recreational activities as a strategy to improve the well-being and motivation of teaching staff, providing a basis for future research aimed at optimizing the work environment in Ecuadorian educational institutions.
Keywords: Recreational activities; work environment; teacher well-being